2011
DOI: 10.1007/s00227-011-1856-7
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenic variations in fatty acid and alcohol composition of the pelagic amphipod Themisto libellula in Kongsfjorden (Svalbard)

Abstract: The fatty acid and alcohol composition of the pelagic amphipod, Themisto libellula, was monitored during the 5 first months of its life cycle (4-20 mm length) in an Arctic fjord, Kongsfjorden, Svalbard. Fatty acids of the three major lipid classes, polar lipids (PL), triacylglycerol (TAG), and wax esters (WE), were analyzed to highlight ontogenic changes in their diet and metabolism. The PL composition of T. libellula did not show any strong variations along their growth except during the first month where an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Significantly higher levels of the diatom-associated FA 16:1(n-7), an important contributor to the FA pool of Calanus spp., in T. libellula during winter further highlights the significance of these copepods for the successful overwintering of T. libellula. The significantly higher relative proportions of the polyunsaturated FAs (PUFAs) 20:5(n-3) and 22:6(n-3) in T. libellula in summer compared to winter (Figures 4A,B) could again point to ontogenetic differences in feeding habits, as the rather omnivorous younger stages (length group 5-20 mm) collected during summer probably fed more intensely on PUFArich phytoplankton/ice algae than the mostly carnivorous adult stages of T. libellula (length group 10-40 mm) (Noyon et al, 2009(Noyon et al, , 2012. However, these PUFAs are mainly incorporated into polar lipids (Stübing et al, 2003), and lower PUFA concentrations in T. libellula in winter might be explained by the larger proportion of storage lipids during the polar night (Supplementary Table 1).…”
Section: Themisto Amphipodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Significantly higher levels of the diatom-associated FA 16:1(n-7), an important contributor to the FA pool of Calanus spp., in T. libellula during winter further highlights the significance of these copepods for the successful overwintering of T. libellula. The significantly higher relative proportions of the polyunsaturated FAs (PUFAs) 20:5(n-3) and 22:6(n-3) in T. libellula in summer compared to winter (Figures 4A,B) could again point to ontogenetic differences in feeding habits, as the rather omnivorous younger stages (length group 5-20 mm) collected during summer probably fed more intensely on PUFArich phytoplankton/ice algae than the mostly carnivorous adult stages of T. libellula (length group 10-40 mm) (Noyon et al, 2009(Noyon et al, , 2012. However, these PUFAs are mainly incorporated into polar lipids (Stübing et al, 2003), and lower PUFA concentrations in T. libellula in winter might be explained by the larger proportion of storage lipids during the polar night (Supplementary Table 1).…”
Section: Themisto Amphipodsmentioning
confidence: 96%
“…In both amphipod species, heterotrophic prey had a greater contribution to their food composition in winter versus summer based on the higher carnivory ratios of 18:1(n-9)/18:1(n-7) and zoosterols to phytosterol ratios (Tables 3, 4). To some extent, the observed seasonal differences likely reflect ontogenetic changes in carbon and prey composition (Noyon et al, 2012), e.g., in T. libellula from early life stages during summer (average dry weight 3.5 mg ind. −1 ) to larger predatory T. libellula individuals during winter (average dry weight 43.4 mg/ind −1 ).…”
Section: Themisto Amphipodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Falk-Petersen et al (2000) demonstrated that the omnivorous T. inermis and T. raschii feed mostly on phytoplankton and small copepods, and that T. longicaudata feeds more heavily on copepods. T. abyssorum, meanwhile, is a pelagic amphipod known to feed on both diatoms and dinoflagellates as well as copepods (Noyon et al 2012, Kraft et al 2013). The phytoplankton biomarkers in fish species sampled here, therefore, likely come from these important omnivorous primary and secondary consumers.…”
Section: Fatty Acids: Benthic Vs Pelagic Carbon Poolsmentioning
confidence: 99%
“…Three hyperiid amphipod species comprise the genus Themisto in northern latitudes: T. libellula, a large Arctic species associated with cold, polar water masses, its subarctic congener T. abyssorum, which is transported to the Arctic by inflowing North Atlantic water masses and T. compressa, a North Atlantic species with its major distribution area in the southern Norwegian Sea (Kraft et al, 2011). Themisto libelulla and T. abyssorum have been studied over the past decade with regard to their food sources, variations in distribution, reproductive strategies, abundances and summer lipid compositions, while little is known about the deepwater species Cyclocaris guilelmi (Bousfield, 1951;Percy, 1993;Koszteyn et al, 1995;Auel et al, 2002;Dalpadado et al, 2008;Marion et al, 2008;Noyon et al, 2009Noyon et al, , 2011Noyon et al, , 2012Kraft et al, 2011Kraft et al, , 2012Kraft et al, , 2013b.…”
mentioning
confidence: 99%